2007
DOI: 10.1002/masy.200750506
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Indomethacin in PVP: Solid‐State NMR Studies

Abstract: 13 C solid-state NMR and 1 H relaxation time measurements have been used to determine the structure of the crystalline and amorphous forms of the pharmaceutical drug indomethacin. Cross-polarization dynamics parameters were calculated for individual NMR resonances providing an insight into the mobility of functional groups in two forms of indomethacin. The changes of mobility in indomethacin/ polyvinylpyrrolidone (PVP) formulation have been investigated via 1 H-13 C solid-state NMR methods. Differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
(10 reference statements)
2
11
0
Order By: Relevance
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Recent studies by Surwase et al reported new crystalline forms of IMC and water driven phase transitions from an amorphous phase, in spite of years of studies. 23 The thermodynamically most stable form of indomethacin (g-IMC) has the space group symmetry P% 1 with Z 0 = 1.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Recent studies by Surwase et al reported new crystalline forms of IMC and water driven phase transitions from an amorphous phase, in spite of years of studies. 23 The thermodynamically most stable form of indomethacin (g-IMC) has the space group symmetry P% 1 with Z 0 = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Possible changes include the interconversion of different crystalline forms, hydrate formation, or chemical degradation. In particular, polymorphic changes of the API, may lead to significant effects on their bioactivity . The stability of the drug formulations is also another fundamental requirement for pharmaceutical development and commercialization .…”
Section: Interfaces In Nanomedicine Complexesmentioning
confidence: 99%
“…24,25 By employing advances in homonuclear 1 H decoupling that deliver high-resolution 1 H spectra, 26,27 the 1 H-1 H DQ CRAMPS technique [28][29][30][31][32] has been applied to the potassium salt of penicillin characterised anhydrous polymorphs (that are labelled ,  and )  crystal structures are available for the  and  forms. 38,39 13 C CP MAS spectra have been reported for the crystalline polymorphs as well as amorphous forms of indomethacin, 13,[40][41][42] while a recent study has presented 1 H- 13 C and 1 H-1 H DQ twodimensional spectra for an indomethacin-polymer dispersion together with a 1 H-1 H DQ MAS spectrum of -indomethacin. 13 Amorphous forms, dispersions as well as co-crystals of indomethacin have and are being extensively studied on account of the poor solubility exhibited by indomethacin and hence its limited bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The observed spectral resonances are assigned by means of GIPAW chemical shift calculations for the full periodic crystal structure (see Table 1) -indomethacin crystallizes in the centrosymmetric triclinic P1 space group with one molecule in the asymmetric unit. Note that the atom numbering system used here is that employed by Basavoju et al; 44 various alternative numbering schemes have been used in the published single-crystal X-ray structure 39 and other reports of solid-state NMR 13 C CP MAS data by Apperley et al, 40 Masuda et al, 41 Guilbaud et al, 42 and Pham et al 13 currents, that lead to  crystmol changes of at least 1 ppm for the 1 H chemical shift (see Table 1) and (e) 53 and host-guest interactions in molecular tweezers [54][55][56] or calixarene complexes. 57 The distance from the particular proton to the centre of the specific aromatic moiety is 2.72 Å (9b) and 3.12 Å (9a) for the C9 CH 2 protons, 2.68 Å for the nearest C11 CH 3 proton and 3.42 Å for the C16 aromatic CH proton.…”
Section: Introductionmentioning
confidence: 99%